Lignin-based polyurethane elastomers - Cateto, Carolina (2011)
The incorporation of lignin into polymeric materials, directly or after chemical modification, is recognized as one of the most viable approaches to accomplish its valorisation and properly exploit its unique intrinsic properties. In this work polyurethanes with elastomeric properties have been synthesised using a three component system based on lignin, 4,4’-methylene-diphenylene diisocyanate (MDI) and polycaprolactone (PCL). The following variables were studied: the lignin type (Alcell (A) and Indulin AT (IAT)), the PCL molecular weight (400, 750 and 1000) and the lignin content (10, 15, 20 and 25% (w/w)). The results pointed out for effective lignin incorporation into the generated polyurethane network, where Alcell has a predominant role of chain extender and Indulin AT acts more as a crosslinking agent.